Pastoralist systems of the Roggeveld in the 18th and 19th centuries - Regensberg, Rae Marilyn (Department of Archaeology, 2016)
Eighteenth and nineteenth century Karoo history has received relatively little archaeological attention. This is despite the fact that the area underwent a major economic transformation in the nineteenth century. The pastoralists of the eighteenth and early nineteenth century Roggeveld predominantly practiced small-scale subsistence farming. This changed rapidly with the introduction of merino wool sheep in the region in the mid 1800s. The region went from small-scale subsistence pastoralism to commercial and global scale Merino wool production, which fully integrated the Roggeveld into the economy of the colony. This dissertation looks at this sequence through the identification and mapping of the infrastructure of pastoralism using Google Earth and begins the process of linking this survey data with refined research on the ground by excavating at one of the sites located on Google Earth.